NARASI SEBAGAI DAYA TARIK MUSEUM SAMSARA LIVING DI JUNGUTAN BEBANDEM KABUPATEN KARANGASEM - Ni Wayan Mekarini; Putu Guntur Pramana Putra (Universitas Triatma Mulya, 2022)
The reseach is held in The Samsara Living Museum in Jungutan Village, Bebandem Distict, Karangasem regency which displays the cycle of Balinese life starting from the fetus in the womb, born, alive, die and cremation. Unfortunately, the collection to display is very limited compared to other museums around. The research followed qualitative approach whereas data collected by observation and interview with informan. Finally, this research found out two conclusions such as (a) The name of Samsara is taken from the phase of reborn and ready to begin another cycle after previous life. Based on this principle, human is suggested to live with care and love but avoid himself to do bad things because the world imply cause-result effect; (b) Realizing the display is limited compared to museum in general, narrative skill is a way to attract more visitors to come. Since it is cultural-based museum, some visitors not knowing well the ritual on display. Here, the guide explained them carefully through suggestive-narrative where the explanation leads listeners to fell involved in the activity and added another meaning, that is cultural meaning. It is delivered slowly to convince visitors so that limited display does not a problem at all.